The health literacy needs of women living with HIV/AIDS - Judy Thompson; Yolanda Havenga; Susan Naude (AOSIS, 2015)
Women in Sub-Saharan Africa are disproportionately affected by the virus and constitute 60% of the total HIV/AIDS infections in this region. Current recommendations endorse the involvement of people living with HIV in the development of programmes for people living with the virus. The purpose of the study was to explore and describe the health literacy needs of women living with HIV. The research design was qualitative, explorative, descriptive and contextual. After women living with HIV/AIDS were sampled purposively, semi-structured interviews were conducted with eight women and qualitative content analysis done. The findings revealed that the women expressed a need to increase their knowledge about HIV/AIDS. The knowledge they needed ranged from basic pathophysiology about HIV/AIDS, to the impact of HIV/AIDS on their health, to an awareness of the modes of HIV transmission and methods of protecting others from being infected. Other important health literacy needs related to self-care and correct antiretroviral use. A need for psychosocial skills was also identified in order for women to build and maintain their relationships. Recommendations were made for nursing practice, education and further research, based on these findings.